(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article examines how engineering graphics and mechanical drafting education can be restructured under conditions of digital transformation. The study analyzes the pedagogical value of integrating artificial-intelligence-assisted tools, computer-aided design environments, augmented and immersive visualization, project-based learning, and standardized graphic tasks for the development of spatial reasoning, drawing accuracy, constructive logic, and industry-relevant competence. A methodological framework is proposed in which manual drafting foundations, parametric modelling, AI-supported feedback, error diagnostics, collaborative design activity, and criterion-based assessment are united into a coherent didactic system. The article argues that digital tools should not be introduced merely as instruments of convenience; they must be treated as pedagogical media that intensify spatial imagination, graphic literacy, technological discipline, and the culture of engineering justification. Based on a synthesis of recent research and a practice-oriented instructional model, the paper formulates recommendations for curriculum design, assessment architecture, teacher preparedness, and academic integrity in higher technical education.